Comparison of Four Bowel Cleansing Agents for Colonoscopy and the Factors Affecting their Efficacy. A Prospective, Randomized Study - Kmochova, Klara; Grega, Tomas; Ngo, Ondrej; Vojtechova, Gabriela; Majek, Ondrej; Urbanek, Petr; Zavoral, Miroslav; Suchanek, Stepan (Journal of gastrointestinal and liver diseases, 2021)
BACKGROUND AND AIMS: Adequate bowel preparation is essential for successful and effective colonoscopy. Several types of cleansing agents are currently available including low-volume solutions. The aim of this study was to compare the efficacy of four different bowel cleansing agents. METHODS: A single-center, prospective, randomized, and single-blind study was performed. Consecutive patients referred for colonoscopy were enrolled and randomized into one of the following types of laxatives: polyethylenglycol 4L (PEG), oral sulfate solution (OSS), 2L polyethylenglycol + ascorbate (2L-PEG/Asc), or magnesium citrate + sodium picosulfate (MCSP). The primary outcome was quality of bowel cleansing evaluated according to the Boston Bowel Preparation Scale (BBPS). Secondary outcomes were polyp detection rate (PDR) and tolerability. RESULTS: Final analysis was performed on 431 patients. The number of patients with adequate bowel preparation (BBPS total scores ≥6 and sub scores ≥2 in each segment) was not significantly different throughout all groups (95.4% PEG; 94.6% OSS; 96.3% 2L-PEG/Asc; 96.2% MCSP; p=0.955). Excellent bowel preparation (BBPS total scores ≥ 8) was associated with younger age (p=0.007). The groups did not have significantly different PDRs (49.5% PEG; 49.1% OSS; 38% 2L-PEG/Asc; 40.4% MCSP; p=0.201). The strongest predictors of pathology identification were age and male gender. The best-tolerated solution was MCSP (palatability: p<0.001; nausea: p=0.024).
Keywords: Polyethylene Glycols; Detergents; mužské pohlaví; Prospective Studies; purgativa; Single-Blind Method; lidé; polyethylenglykoly; Humans; detergenty; prospektivní studie; Male; Cathartics; jednoduchá slepá metoda; kolonoskopie; Colonoscopy